1996
DOI: 10.1002/eji.1830260819
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for intact CD28 signaling in T cell hyporesponsiveness induced by the HIV‐1 nef gene

Abstract: Infection by human immunodeficiency virus (HIV)-1 is associated with quantitative and qualitative T cell alterations that severely impair the host's immune defense system. The molecular basis for this immunosuppression remains unclear. Peripheral blood mononuclear cells (PBMC) isolated from patients show markedly decreased interleukin (IL)-2 secretion but unaffected or even increased T helper (Th)2 cytokine production. T cell functional defects were recently reported to correlate more with T cell receptor (TcR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Yet another series of studies indicated that Nef had no effect on NF-κB: Collette et al . observed that CD28 signaling did not contribute to Nef-mediated modulation of IL-2 [75], and Yoon et al . reported that there was no influence of Nef on NF-κB or AP-1 [65].…”
Section: Regulation Of Key Transcription Factors and Signaling Moleculementioning
confidence: 99%
See 1 more Smart Citation
“…Yet another series of studies indicated that Nef had no effect on NF-κB: Collette et al . observed that CD28 signaling did not contribute to Nef-mediated modulation of IL-2 [75], and Yoon et al . reported that there was no influence of Nef on NF-κB or AP-1 [65].…”
Section: Regulation Of Key Transcription Factors and Signaling Moleculementioning
confidence: 99%
“…One related study found that stimulation with anti-CD28 did not affect Nef’s inhibitory role [75]. By contrast, later studies have employed anti-CD3 and anti-CD28 that are either cross-linked [39,40,42,44,53], presented on beads [45,66,159] or bound to coverglass to mimic the immune synapse [86]; however, the stimulation dose in these assays may not reflect biological interactions with APC.…”
Section: Making Sense Of Discrepancies In the Literaturementioning
confidence: 99%
“…Finally, simian immunodeficiency virus strains with Nef variants harboring amino acid sequences that resemble immunoreceptor tyrosinebased activation motifs could replicate to high levels in peripheral blood mononuclear cells without a need for exogenous stimulation (9). Contrasting with these results, other reports have suggested that Nef inhibits lymphocyte activation (10)(11)(12)(13)(14)(15)(16)(17)(18)(19): for instance, in Jurkat cell clones stably expressing HIV-1 nef (10)(11)(12)(13)(14) or electroporated with recombinant nonmyristoylated Nef (15,16). However, interpretation is complicated by the possible selection of cells tolerized for Nef (10,14) or the improper subcellular localization of nonmyristoylated Nef (15,16).…”
mentioning
confidence: 98%
“…However, interpretation is complicated by the possible selection of cells tolerized for Nef (10,14) or the improper subcellular localization of nonmyristoylated Nef (15,16). Two other studies relied on an inducible system, but the inducing agent was phorbol myristate acetate (PMA), itself a major modulator of T cell activation (17,18).…”
mentioning
confidence: 99%
“…Both the HIV-1 Tat and Nef have been demonstrated to inhibit proliferation of T-cells (Viscidi et al, 1989;Collette et al, 1996b;Wrenger et al, 1997). To assess whether this would also be the case for the related SIVmac Tat and Nef proteins, PBMC of vaccinated (691 and 3152) or infected (22M and 25M) macaques known to have positive proliferative responses to p27 Gag were tested in a proliferation assay with the p27 Gag in the presence or absence of native or heat-inactivated Tat and Nef proteins.…”
Section: The Sivmac Purified Nef and Tat Proteins Inhibit P27 Gag-drimentioning
confidence: 99%